On the absolute continuity of mappings distorting the moduli of cylinders - Salimov, R. R.; Sevost'yanov, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We consider the mappings satisfying one modular inequality with respect to cylinders in the space. The distortion ofmodulus is majorized by an integral depending on a certain locally integrable function. We also prove a result on theabsolute continuity of the analyzed mappings on lines.